Influence of the content of complex additives on the deformation properties of cement - Svetlana V. Samchenko; Dmitriy A. Zorin; Nguyen D.T. Lam; Tang V. Lam (Stroitel’stvo: Nauka i Obrazovanie, 2023)
Introduction. When using concrete and reinforced concrete structures, it is necessary to overcome problems associated with the quality of concrete to shrink in size and experience shrinkage during hardening and drying. To solve problems with shrinkage, special attention is paid to the materials that, when added to ordinary portland cement, make it possible to obtain non-shrinkable, expanding types of cements. A well-known way of producing expanding cements is to grind cement clinker, gypsum and a special additive together. In addition, the introduction of active mineral additives with pozzolanic properties allows to compact the structure of the cement stone, reduce porosity, increase strength and reduce shrinkage. They also save the clinker for the cement production, help to reduce the cost of production and help to reduce the burden on the environment. One of these mineral additives is tripoli.Materials and methods. The effect of additives content on the deformation property of the composite binger was studied using the experiment planning method. Deformation of cement at the age of 2, 3, 7, 14 and 28 days were determined in accordance with the method of results processing in accordance with GOST R 56727–2015, GOST 11052–74. The research was carried out in the laboratory of the Department of Construction Materials Science of the Moscow State University of Civil Engineering.Results. The results obtained are presented as the surface of a second level regression equation describing the dependence of the blinder deformation on the content of complex expanding and pozzolanic additives. As a result of the experiments conducted, the composition with the maximum expansion and the composition with maximum shrinkage using complex additives were obtained. The results will be further used to predict the deformation properties of the binder.Conclusions. Based on the results of this study, the authors will continue to study the properties of binders based on a complex expanding and pozzolanic additive in the future.